Utilization of Hands Free Wash Basin as Covid-19 Prevention in Public Health Center - Hutabarat, Nauas Domu Marihot Romauli; Ambarita, Himsar; Sinamo, Karina Nola (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Simalingkar Public Health Service is located in one of one of the 5 districts in Medan with the Red zone status. At the Partner location, it was found that they using hand wash basin with ordinary hand operated tap and it was not optimal to preventing the spread of the Covid-19 virus since some surface of plastic or steel in public health service cannot absorb droplet and preserving the active virus, it could become the transmission vehicle of the virus from one person to the next. Because that area with high touch intensity can pose a risk of transmission of the Covid-19 virus, the solution that will be offered by designing and making an automatic tap hand wash basin by using feet pedals so that there is no need hand to touch the water tap The purpose of this activity is expected that Partners can preventing the spread of Covid-19 by using hands free wash basin on daily health service activities.